The Implications Of Human Resource Competencies and Benchmarks on Employee Performance Through Organizational Citizenship Behavior a Study at Sultan Hadlirin Islamic Hospital, Jepara - Aditya Angger Wibowo (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
This study aims to analyze the influence of human resource competencies and benchmarks on employee performance through the moderating effect of Organizational Citizenship Behavior (OCB). The urgency of this study stems from the phenomenon of employee turnover, which necessitates extra-role behavior to maintain the stability of healthcare services. A quantitative approach was applied involving 242 respondents at Sultan Hadlirin Islamic Hospital in Jepara, selected through purposive sampling. Data analysis was conducted using the Structural Equation Modeling (SEM) method with AMOS 31 software. The primary focus of this study is to dissect the causal mechanisms through which individual capacity and HR benchmarks translate into superior performance outcomes within the hospital ecosystem. The results of the structural analysis indicate that employee competence and HR benchmarks make a positive and significant contribution to strengthening OCB. Furthermore, the empirical findings confirm that employee competence, HR benchmarks, and OCB simultaneously serve as substantial predictors in significantly improving employee performance. OCB has been identified as a crucial pathway linking personal competence and organizational standards to collective performance outcomes. The practical implications of this study emphasize the importance of hospital management in optimizing sustainable capacity development and standardizing exemplary work behavior. These strategic steps are necessary to foster a culture of voluntary work that is responsive to HR dynamics, thereby ensuring that the quality of medical services is maintained amidst the challenges of workforce turnover.